2013
DOI: 10.1371/journal.pone.0066005
|View full text |Cite
|
Sign up to set email alerts
|

Link Clustering with Extended Link Similarity and EQ Evaluation Division

Abstract: Link Clustering (LC) is a relatively new method for detecting overlapping communities in networks. The basic principle of LC is to derive a transform matrix whose elements are composed of the link similarity of neighbor links based on the Jaccard distance calculation; then it applies hierarchical clustering to the transform matrix and uses a measure of partition density on the resulting dendrogram to determine the cut level for best community detection. However, the original link clustering method does not con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 23 publications
(71 reference statements)
0
23
0
Order By: Relevance
“…An extended link clustering method is presented in [4]. The algorithm runs extended link similarity and uses EQ metric for finding the top quality for the hierarchical clustering dendrogram part.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…An extended link clustering method is presented in [4]. The algorithm runs extended link similarity and uses EQ metric for finding the top quality for the hierarchical clustering dendrogram part.…”
Section: Related Workmentioning
confidence: 99%
“…After getting biased, new candidates are specified. Power of each group is computed according to these candidates using equation (4). Inter-group competition starts after intra-group competition.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…c be a child of 1 c , 4 c be a child of 2 c , 8 c be a child of 4 c , 5 c be a child of 8 c , and for a child of 5 c , let j be the child of node i, as in the above search order, Because the search sequence according to the above discussion, it has a neighbor node logic is no subsequent child nodes, so that it does not have children, and then 3 c is a child of 1 c , is a child node, the same 7 c is a child of 3 c , 6 c and 7 c has no child nodes. If j is a child of node i ,then A defines the search number of the earliest node in the subtree of j that can be traced back to node i by non-parent-side edges (i and j sides).…”
Section: ( )mentioning
confidence: 99%
“…However, it is found that complex networks are not scale-based networks, but are not stochastic networks [2,3] . Therefore, the previous experience in identifying and protecting critical nodes is not suitable for complex networks with robustness, fragility and scale-free characteristics [4,5] , There is an urgent need for new methods and techniques to carry out research. In this paper, the key nodes in wireless sensor networks are probed, so it is assumed that the graphs formed by all the nodes and each node and its neighbor nodes are connected in advance, so we need to give the concept of graph traversal [6,7] .…”
Section: Introductionmentioning
confidence: 99%